Answer:
300 divided by 500 is 0.6
S is step-by-step explanation:
Answer: Currently 8 action films are being shown
Step-by-step explanation:
Step 1
Ratio of action film to other films = 1:2
which means 1 action movie would be shown for every 2 other films
Total ratio = 1+2 = 3
Step 2
Number of action films shown = ratio of action film/ total ratio x 24 screens
= 1/3 x 24 = 8
Number of other films shown = ratio of other films/ total ratio x 24 screens
= 2/3 x 24 = 16
Currently 8 action films and 16 other films are being shown
A. -26 B.-9 C. -1 D. 10
The value of g(f(-3)) would be -9 which is the correct answer would be an option (B).
A function is defined as a mathematical phrase that specifies a connection between two variables in algebra.
We have been given the functions below as
f(x) = 3x + 7 and g(x) = 2x - 5
We have to determine the value of g(f(-3))
Substitute the value of f(x) = 3x + 7 in the g(x) = 2x - 5 to get g(f(x))
⇒ g(f(x)) = 2(3x + 7) - 5
Apply the distributive property of multiplication,
⇒ g(f(x)) = 6x + 14 - 5
⇒ g(f(x)) = 6x + 9
Substitute the value of x = -3 in the g(x) = 2x - 5 to get g(f(-3))
⇒ g(f(-3)) = 6(-3) + 9
⇒ g(f(-3)) = -18 + 9
⇒ g(f(-3)) = -9
Therefore, the value of g(f(-3)) would be -9.
Learn more about the functions here:
#SPJ1
The expression 3z+4 = 4+3z represents the commutative property of addition.
The cumulative property states that if the position of the numbers when they are in addition is changed then it will not affect the final result of the addition. If altering the operands' order has no effect on the outcome, the binary operation is commutative in mathematics.
The commutative property basically states that x+y can be flipped yet have the same meaning so x+y = y+x ~
The given expression 3z+4=4+3z is showing the cumulative property of addition. By changing the position of the additional terms the final result will not change.
Therefore, the expression 3z+4 = 4+3z represents the commutative property of addition.
To know more about cumulative property follow
#SPJ2
Answer:
B = (2, -5)
Step-by-step explanation:
The problem requirements mean ...
B - A = (2/3)(C - A)
B = A + (2/3)C - A
B = (1/3)A + (2/3)C = (A +2C)/3
B = ((-6, 1) +2(6, -8))/3 = (-6+12, 1-16)/3 = (6, -15)/3
B = (2, -5)
/12
2
-0.1/144
√43
57
10
Answer:
the answer is 01
Step-by-step explanation:
Answer:
01
Step-by-step explanation:
2
no solutions
or
infinitely many solutions
solve the equation by completing the square. round to the nearest hundredth. x^2+6x=-7
4.41,1.59
-4.41,1.59
-4.41,-1.59
4.41,-1.59
and the last one is
solve the systems of equations algebraically. show all of your steps.
y=x^2+2x
y=3x+20